1988
DOI: 10.1021/ja00218a023
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the insertion of olefins into niobium- and tantalum-hydride bonds: a study of the competition between steric and electronic effects

Abstract: The mechanism of insertion of olefins into transition metal-hydride bonds has been examined for a series of olefin hydride complexes of niobocene, permethylniobocene, tantalocene, and permethyltantalocene. The insertion rates were measured for several meta-substituted styrene complexes of permethylniobocene and found to be comparable to those found for the para-substituted analogues, indicating that the electronic effects are largely inductive in origin. An X-ray crystal structure determination for the parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 2 publications
7
87
1
Order By: Relevance
“…The reverse reaction in Equation (4) represents ethylene insertion into the Ti1H bond. This is the "standard" chain initiation reaction; its rate constant, k E i , is usually assumed to be equal to or higher than the propagation rate constant k E p in Equation (6) [29,30] Chain Initiation Reactions Involving Ethylene and a-Olefin…”
Section: Formation Reaction Of Initial Catalytically Active Ti1et Andmentioning
confidence: 99%
“…The reverse reaction in Equation (4) represents ethylene insertion into the Ti1H bond. This is the "standard" chain initiation reaction; its rate constant, k E i , is usually assumed to be equal to or higher than the propagation rate constant k E p in Equation (6) [29,30] Chain Initiation Reactions Involving Ethylene and a-Olefin…”
Section: Formation Reaction Of Initial Catalytically Active Ti1et Andmentioning
confidence: 99%
“…The insertion of olefins into metal-hydride bonds [16] and its microscopic reverse, b-elimination, are very common steps in industrial catalytic reactions such as olefin isomerization, hydrogenation, and hydroformylation.…”
Section: Insertion Processes With Alkenesmentioning
confidence: 99%
“…been observed that electron-releasing 4-R-substituents accelerate migration [14], presumably by stabilizing the modest accumulation of positive charge at C b in the transition state for the migration.…”
Section: The Mechanism Of the Reactions Of [Ni(g 2 -Ch 2 C 6 H 4 R-4)mentioning
confidence: 99%